Colonization of methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococci and its associated factors in cancer patients at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Eden Getaneh Mekonnen; Abebe Birhanu; Mulugeta Yimer; Segenet Bizuneh; Mucheye Gizachew; Baye Gelaw (PLoS ONE, 2025)
Background Cancer patients are predisposed to methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococci colonization. However, the prevalence of these pathogens among cancer cases in Northwestern Ethiopia remains underreported. Objective To determine the prevalence of colonization of methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococci and associated factors among cancer patients at the University of Gondar Comprehensive Specialized Hospital, Northwestern Ethiopia. Method A cross-sectional study enrolled 288 confirmed cancer participants through stratified systematic random sampling, gathering socio-demographic and clinical data via pretested structured questionnaires from May 1 to July 30, 2023. Each participant provided two specimens: a nasal swab and a fecal sample. Nasal swabs were collected using sterile swabs, inserted at least 1 cm into each nostril, and rotated against the nasal membrane for 10 to 15 seconds, which were then placed in Amies transport medium. Fecal specimens were collected in leak-proof plastic containers, swabbed, and transferred to Cary Blair transport medium. Nasal swabs and fecal specimens were cultured on Mannitol salt agar at 37°C for Staphylococcus aureus identification, which was confirmed by coagulase testing and Gram staining. Enterococci were cultured on Bile esculin agar at 43°C and identified at the genus level by cultural characteristics, with confirmation through Gram reaction and catalase tests. Antibiotic susceptibility was evaluated using the Kirby-Bauer disk diffusion method, with minimum inhibitory concentrations for vancomycin determined via E-test strips. To detect methicillin-resistant Staphylococcus aureus, a cefoxitin disk was used. Inducible clindamycin resistance in Staphylococcus aureus was determined by the D test. Epi-info version 7 and SPSS version 27 were used for data entry and data analysis, respectively. The Pearson Chi-Square test was initially used to evaluate the association between factors and outcomes as the preliminary analysis, with a significance threshold of p <  0.05. Variables meeting this criterion underwent bivariable and multivariable logistic regression analyses, using p-value cutoffs of <  0.2 for bivariable and <  0.05 for multivariable analyses. Result The study involved 288 participants, with 51.0% being men and a mean age of 45.6 years. The prevalence of methicillin-resistant Staphylococcus aureus was 11.1% (95% CI: 7.5–14.7%), while vancomycin-resistant Enterococci had a prevalence of 2.8% (95% CI: 0.9–4.7%). Inducible clindamycin-resistant Staphylococcus aureus comprised 13.5% of the isolates. The multidrug-resistant proportion of Staphylococcus aureus and Enterococci were 56.2% and 55.2%, respectively. Both organisms exhibited the highest resistance to the antibiotic classes of penicillin and tetracycline. Significant associations were identified between methicillin-resistant Staphylococcus aureus colonization and low absolute neutrophil count (AOR =  13.050, 95% CI: 1.362-125.00, P =  0.026), and between vancomycin-resistant Enterococci colonization and having undergone an invasive procedure (AOR =  8.648, 95% CI: 1.870-39.992, P =  0.006). Conclusion The study reveals a significant prevalence of methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococci colonization among cancer patients, raising public health concerns. High antibiotic resistance rates complicate treatment and may impact patient outcomes. Notably, the high inducible clindamycin resistance report, highlights the need for D-testing. Screening for methicillin-resistant Staphylococcus aureus is recommended as an important antibiotic stewardship measure, while early detection of vancomycin-resistant Enterococci colonization is crucial to reduce complications.